Short and long-term behaviour of RC slabs strengthened with prestressed CFRP laminate strips - Sena-Cruz, José (2017)
In the context of strengthening reinforced concrete (RC) structures with fiber reinforced polymer (FRP) materials, the externally bonded reinforcement (EBR) technique is the most widely used strategy. By prestressing the FRP materials attached to the concrete substrate, the advantages of external prestressing and of the EBR technique are combined. The solutions adopting carbon FRP (CFRP) laminates have been mostly used. Special end-anchorage systems are required at the ends of the prestressed CFRP laminate to transfer the high shear stresses developed from the FRP to concrete, in order to avoid a premature FRP peeling-off failure. From all the proposed systems, two of them have been prevailed, mainly: the mechanical anchorage (MA) fixed to the ends of the FRP reinforcement and the gradient anchorage (GA). The present work investigates the short and long-term behaviour, including the durability issues, of reinforced concrete (RC) slabs strengthened with prestressed CFRP strips according the EBR technique. Two different anchorage systems were studied: (i) MA and (ii) GA. The experimental program carried out included of the effects of environmental actions such as water, water with chlorides and wet-dry cycles on the global performance of these slabs. This paper presents the general description of the experimental program, the analysis of the main results, as well as the retained conclusions.